Ilmenite megacryst-hosted melt inclusions from the Monastery kimberlite: implications for kimberlite origins - Van Huyssteen, Aiden (Rhodes University, Faculty of Science, Department of Geology)
Polymineralic inclusions encapsulating a daughter assemblage of crystalline phases (including silicates, oxides, and carbonates) and an amorphous glass phase, hosted in ilmenite megacrysts from the Monastery kimberlite, were investigated texturally and geochemically in order to constrain their melt origin, modeof formation, and evolution prior to quenching. The isolated nature of the melt inclusions within the ilmenite megacrysts provides an opportunity to study components of primary kimberlitic magma captured within the SCLM (4.5"“6 GPa) that has been isolated from pervasive modifying processes that are common in kimberlites. The common daughter phase assemblage within the melt inclusions comprises serpentine, phlogopite, calcite, spinel, kassite, perovskite, ilmenite, and glass. The glass is Si-Mg-Fe-rich, with low Al2O3 contents. It is also K2O- and TiO2-free, with variably depleted REE. In composition, serpentine forms a crystalline equivalent to the glass. However, these phases are optically distinct. Serpentine represents two modes of formation: (i) discrete euhedral grains set within a glass matrix that represent a primary phase, crystallising directly from the entrapped melts, and (ii) as patches of partially crystallised glass that represent a secondary phase formed by the devitrification of the glass. Spinel and phlogopite form along early kimberlitic evolutionary trends and record the depletion of the melt in TiO2, Al2O3, and K2O, which typically decreases from the core to the rim of the crystals. Volatile and alkali-bearing minerals (calcite, apatite, phlogopite) crystallised within the melt inclusions from the captured alkali-rich carbonated-silicate kimberlite melt. The daughter mineral assemblage initially crystallised as euhedral and subhedral grains with a uniform composition under equilibrium conditions. Subsequent crystallisation formed grains that exhibit magmatic zoning due to their crystallisation in a progressively depleted melt. Lastly, the crystallisation of skeletal oxide grains occurred under disequilibrium conditions, at a stage of magma ascent with rapidly changing variables including temperature, melt viscosity, and diffusivity. Prior to complete crystallisation, the residual Si-Mg-Fe melt of this crystallisation process was quenched to form the observed glass. The phases that constitute the common daughter assemblage show large variations in modal proportions, forming a continuum from silicate-rich to carbonate-rich endmember inclusions, with certain daughter phases absent in some inclusions. This suggests that the melt was heterogenous at the time of capture and comprised immiscible silicic/oxidic and carbonate melts. Phase separation, therefore, may have started prior to capturing of magma batches as inclusions in ilmenite, but further segregation and crystallisation continued after these batches had become isolated from the megacryst matrix as melt inclusions. The immiscibility and co-existence of the silicic/oxidic and carbonate melts is preserved by textural features between calcite and glass, such as rounded globules of calcite grains set within a silicate glass matrix, calcite forming the matrix for euhedral silicate and oxide minerals, and calcite occupying the interior void of skeletal oxide grains set within a silicate glass matrix. Furthermore, spherulitic globular domains of Ca- and Ti-rich glasses set within a matrix of the Si-Mg-Fe glass suggest that the silicic/oxidic melt underwent further segregation into oxide-rich (Ca-Ti) and silicate-rich (Si-Mg-Fe-Al-K-Ti) melts, potentially crystallising the oxide and silicate minerals of the daughter assemblage, respectively. The abundance of incompatible trace elements and the Cr-poor composition of secondary low-Mg ilmenite as a daughter mineral within the melt inclusions (~1400 ppm Nb; <0.1 wt% Cr2O3; <0.1 wt% MgO), in addition to the Cr-poor composition of the other daughter phases within the inclusions (i.e. <0.1 wt% Cr2O3 for phlogopite and spinel), indicate that they crystallised from a similar melt as the Cr-poor, but high Mg-ilmenite megacrysts (~1400 ppm Nb; <0.1 wt% Cr2O3; ~10 wt% MgO). Furthermore, the melt inclusions are randomly distributed and no textural and/or geochemical evidence for melt infiltration of the ilmenite megacrysts was associated with the melt inclusions. These features are consistent with a primary origin for the melt inclusions which implies a cognate relationship between the megacrysts and the captured kimberlite melt.
Keywords: Uncatalogued